Brachial Plexus Block with Use of a Neurostimulator in a Striped owl (Asio clamator) Undergoing Wing Amputation - do Nascimento, Felipe Medrado; Nunes, Talyta Lins; Silva Souza, Thamires Barreto; Couto Andrade, Marcio de Almeida; Barbosa, Vivian Fernandes (Acta Scientiae Veterinariae, 2019)
Background: The use of distinct drugs and techniques for establishing balanced anesthesia protocols has shown promising results in birds. The techniques of locoregional block can be incorporated to these protocols, thereby providing intra- and post-operative analgesia and reducing the requirement for general anesthesia. Additionally, the use of neurostimulators increases the chances of success and reduces the risk of toxicity; however, there are limited reports in the literature of its applicability in wild birds. Therefore, the aim of this study was to describe the brachial plexus block technique guided using a neurolocalizer in a striped owl (Asio clamator) submitted for right wing amputation. Case: A striped owl weighing 400 g with a history of exposed fracture of the right wing was supplied by the clinical sector at the Veterinarian Hospital of the Federal University of Bahia. Following hydration and stabilization of vital signs, the animal was referred to the surgical center for amputation of the limb. Dexmedetomidine (10 µg.kg−1 IM) was administered as premedication, and after 20 min, anesthetic induction was performed using sevoflurane (FiO2 = 100%) via a mask followed by maintenance using the same drug. The animal was positioned in a left lateral decubitus position with access to the brachial plexus determined by palpation and identification of the border of the following muscles: pectoral, cranial branch of the brachial biceps, and dorsal branch of the ventral serratus. The brachial plexus nerves are situated in the subcutaneous site craniodorsal to the axillary depression. For the block, a neurolocalizer was used, fixing the positive electrode to approximately 5 cm from the needle insertion site (21G × 2’”) in the axillary depression, which remained connected to the neurostimulator by the second electrode. At first, the needle was attached to the peripheral nerve stimulator using a pulse frequency of 1 Hz with an impulse duration of 0.1 ms and initial current of 1 mA. The needle was advanced in the direction of the nerve plexus until it was observed that muscular contractions and movement in the limb were blocked, gradually decreasing the contractions, which disappeared at a current of 0.3 mA. At this juncture, after verifying the absence of blood on aspiration, ropivacaine was injected (2 mg/kg) with a latency period of 20 min. Data were recorded via monitoring of vital signs (DigicareLifeWindowLW9xVet), recording an average hearth rate of 140 ± 9.84 bpm, respiratory rate of 30 ± 4.18 mpm, oxyhemoglobin saturation of 99%, end-tidal carbon dioxide of 26 ± 1.98 mmHg, and temperature of 37.4°C ± 0.11°C over the course of 20 min of the surgical procedure. No movements were observed in response to pain stimuli, and the animal exhibited normal recovery, free of excitation or signs of pain. Discussion: Considering the imprecise history regarding fracture time as well as the lack of specific tests to clearly elucidate the condition of this animal, selective and safe drugs were selected additionally: dexmedetomidine and sevoflurane, which provided superior quality of sedation during the handling of the animal and rapid and smooth anesthetic induction, respectively. Based on experiences with numerous species, the inclusion of the locoregional block has substantial value for lengthening the analgesic duration and quality in addition to reducing adverse effects inherent in general anesthesia. In the present study, the use of ropivacaine in the brachial plexus block with the use of a neurolocalizer in the striped owl was demonstrated to be easy to perform using the axillary approach, demonstrating efficacy confirmed by the stability of physiological variables and muscle relaxation as well as the absence of adverse events during recovery.